The Death of Newspaper in the Perspective of Autopoietic Systems Niklas Luhmann (Case Study of Sinar Harapan Newspapers) - Kun Sila Ananda (2021)
Recently in Indonesia, the number of newspapers keep declining while at the same time, more online media emerge. One of the newspapers that has stopped publishing was the legendary evening newspaper Sinar Harapan, which stopped printing in 2016. This study aims to analyze the Ã¢â‚¬Å“deathÃ¢â‚¬Â of the evening newspaper Sinar Harapan from the perspective of Niklas LuhmannÃ¢â‚¬â„¢s autopoietic system. Luhmann considers mass media as an autopoietic system that must have certain characteristics in order to survive. This research using case study methods with history perspective. The data were collected using the literature study method. This research shows that the evening newspaper Sinar Harapan as an autopoietic system has to stop operating because of the complexity of the environment that Sinar Harapan cannot compensate for. Although Sinar Harapan has carried out an evolutionary process on the selection stage, it has failed to stabilize itself. On the other hand, Sinar Harapan also failed to carry out its function as a media system to always present novelties irritating the social system.